Women and political participation in Brazil - Barros, Marilene (REVISTA AGON - Ἀγών - ISSN: 2965-422X, 2023)
Women in Brazil have gained a tremendous impetus in political participation since the transition to democracy. Political participation increased not only in terms of increased women’s participation in voting, but also in official political positions in Congress and in executive ministries. Up until now, the entrance of women into Brazilian politics has been examined in a broad manner that highlights women’s participation in social movements and the broad characteristics of their participation in institutions dominated by men. The introduction of laws that pertain to the protection of women’s rights has been one of the central issues that women have been able to advance, although there have certainly been obstacles to their implementation. However, I argue that it is important to look in more depth at the achievements of elected women both with respect to the personal problems they have confronted in their chosen careers (particularly the discrimination and the extent to which they have to prove that they are hardworking and smart people) and with respect to the professional obstacles during their tenures in office.